O que pensam crianças de seis a nove anos de idade sobre os anos iniciais de uma escola do Ensino Fundamental: uma leitura walloniana - Monteiro, Shirlei Nadaluti (2022)
This doctoral research aimed at investigating what children think and how they feel about starting public elementary school. Specific objectives sought to identify joy, tension and difficulties pointed by children to investigate their expectations towards this new school phase, and which daily activities cause them well-being or ill-being sensations. We also aimed to know children’s feelings during the return to in-person classes, after the pandemic. This qualitative study is based on the legitimacy of children’s words and their importance to understanding experiences inside and out of schools. Theoretical basis is rooted in the theory of French doctor, psychologist and educator Henri Wallon, who proposed the psychogenetic approach of human development, understanding man through a thorough view, contextualized by the relationships established within their environment. Method is sustained by the studies and research of Maria da Conceição Passeggi, used as inspiration in the perspective of children’s narratives. The source of information was narratives developed by children attending the early years of a public elementary school in the city of São Paulo. Production of such information happened in two phases: the first, during 2019, before social distancing and suspension of in-person classes due to the coronavirus pandemic, with first-year students. The second, after the return of in-person classes, during the second semester of 2021, when the same children were attending the third year of elementary school. Data analysis was also divided in two phases: for the first phase, categories of analysis, called Episodes/Categories, were developed from collective narratives produced by the children. Results showed that children are capable of presenting opinions about the school, its times and spaces, teacher methodologies and their friends. For the second phase of analysis, based on the children’s individual narratives, a chart portraying pleasant and unpleasant feelings was created. Such analysis showed that children developed learning, even while away from school, and that the pleasant feelings overcame unpleasant feelings when inperson classes returned